Nutrient digestion and utilization in farm animals: modelling approaches - Kebreab, E.; Bannink, A.; Bannink, A.; Dijkstra, J.; Dijkstra, J.; France, J.; France, J.; Gerrits, W. J. J.; Gerrits, W. J. J.; Kebreab, E. (Wallingford :CABI Publishing, 2006)
This book contains 34 chapters on nutrition physiology and presents scientific research in modelling nutrient digestion and utilization in domestic animals, including cattle, sheep, pigs, poultry and fishes. It is divided into 6 parts that cover fermentation, absorption and passage; growth and development; mineral metabolism; methodology and model development; environmental impacts and animal production and feed evaluation models. Deterministic, stochastic, empirical and mechanistic modelling approaches are also described. This book will be of significant interest to researchers and students of animal science, especially those concerned with nutrition modelling.
Keywords: AA500 - Research; LL510 - Animal Nutrition (Physiology); LL520 - Animal Nutrition (Production Responses); PP600 - Pollution and Degradation; RR300 - Feed Composition and Quality; XX100 - Animal Wastes; ZZ100 - Mathematics and Statistics